The impact and spatial effect of rural revitalization on agricultural carbon dioxide emissions: a case study of Henan Province - Zhao, Jincai; Du, Yongmeng (Frontiers in Environmental Science, 2023)
Clarifying the influencing mechanism of rural revitalization on agricultural carbon emissions is crucial for attaining carbon peaking and carbon neutrality. Using panel data collected from 18 cities at the prefecture level in Henan Province from 2001 to 2020, this study examines the temporal and spatial dynamics of agricultural carbon emissions. A spatial econometric model is employed to explore the influence and spatial impact of rural revitalization on carbon emissions from agricultural land. Additionally, the mediating effect is utilized to examine the mechanism of rural revitalization affecting agricultural carbon emissions. These results indicate that rural revitalization exerts a notable beneficial influence on carbon emissions in Henan Province, as its improvement results in a rise in such emissions. Furthermore, rural revitalization demonstrates a favorable spatial diffusion impact on agricultural greenhouse gas emissions in neighboring urban areas. Agricultural GDP and mechanical technological progress act as intermediate factors, as rural revitalization promotes carbon emissions from agriculture by fostering economic development and technological advancements. Heterogeneity analysis indicates that the correlation between rural revitalization and greenhouse gas emissions from agriculture is nonlinear, as moderate and low levels of rural revitalization promote agricultural carbon emissions, while higher levels exhibit a negative effect. Thus, rural revitalization exhibits an inflection point effect on agricultural carbon emissions.